Analisis Pemasaran dan Transmisi Harga Lada Putih di Kabupaten Sambas - Arifin, Nur; Suyatno, Adi; Fitrianti, Wanti (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Marketing channels, marketing margins, efficiency and elasticity of marketing price transmission for white pepper in Sambas Regency will be the objectives of this research. Quantitative descriptive methods were used in this research. Non-probability sampling is a technique used with the purposive sampling method. Primary and secondary sources are the data used. Marketing margin analysis, marketing channel efficiency, and price transmission elasticity are some of the methods used. The results of this research show that there are two different marketing channels for white pepper in Sambas Regency: channel I directly from farmers to wholesalers then to final consumers, and channel II from farmers to collectors then to wholesalers then to final consumers. Channel I marketing efficiency is 0.46% and farmer's share is 97.56%, resulting in a marketing margin of IDR 2,000/kg. At the same time, marketing channel II achieved a marketing margin of Rp. 5,000/Kg, with a farmer's share of 93.90% and a marketing efficiency level of 0.83%. Marketing channel I is more efficient than marketing channel II. The elasticity value of price transmission in channel II is 0.663, which means that every 1% change in consumer prices will cause a change of less than 1% or 0.663% change in producer prices so it is inelastic. On the other hand, the collector level and producer level have an elasticity value of 0.632, meaning that a 1% change at the collector level results in a price change of 0.632% or less than 1% at the producer level (Inelastic). Thus, the influence of consumer prices is greater than collector prices.